The example of Burkina Faso Food or biofuels. Must we choose? - Dabat, Marie-Hélène; Blin, Joël (Perspective, 2011)
<span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"Would the Southern countries benefit from producing biofuels? This is the subject of heated debate. For some, biofuels are a factor of development; for others, they compete with food production. Proand anti-biofuel positions are based as much on personal beliefs as on substantiated arguments. The case of Burkina Faso demonstrates how this question can be answered at country level."}" data-sheets-userformat="{"2":585,"3":[null,0],"6":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"12":0}">Version française de l'article <span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"Would the Southern countries benefit from producing biofuels? This is the subject of heated debate. For some, biofuels are a factor of development; for others, they compete with food production. Proand anti-biofuel positions are based as much on personal beliefs as on substantiated arguments. The case of Burkina Faso demonstrates how this question can be answered at country level."}" data-sheets-userformat="{"2":585,"3":[null,0],"6":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"12":0}">Would the Southern countries benefit from producing biofuels? This is the subject of heated debate. For some, biofuels are a factor of development; for others, they compete with food production. Proand anti-biofuel positions are based as much on personal beliefs as on substantiated arguments. The case of Burkina Faso demonstrates how this question can be answered at country level.